2016
DOI: 10.1007/s10897-016-0029-8
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Genetics of Intracranial Berry Aneurysms and Implications for Genetic Counseling

Abstract: Here we review the current understanding of the genetic architecture of intracranial berry aneurysms (IBA) to aid in the genetic counseling of patients at risk for this condition. The familial subtype of IBA, familial intracranial aneurysms (FIA), is associated with increased frequency of IBA, increased risk of rupture, and increased morbidity and mortality after rupture. Family history is the strongest predictor for the development of IBA. However, a genetic test is not yet available to assess risk within a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 124 publications
0
29
1
Order By: Relevance
“…Intracranial tumor is caused by many factors, and intracranial atherosclerosis-induced degradation of arterial wall and the occurrence of inflammatory reaction is the main reason. The treatment of intracranial hemangiomas by intracranial vascular embolization increased in the 1970s, and intracranial vascular embolization and craniotomy are the most common means of treatment of intracranial aneurysms ( 10 , 11 ). In this study, by comparing the impact of vascular interventional embolization and craniotomy on patients with intracranial aneurysms, the results showed that i) vascular interventional embolization can effectively increase the 3-year survival rate of patients with intracranial tumors, and significantly reduce postoperative adverse reactions; ii) vascular embolization can effectively reduce the levels of intravascular ROS and proinflammatory cytokines, and increase the level of inhibitors, which can effectively control the intracranial inflammatory response; iii) vascular embolization can effectively reduce the serum levels of MMP-2, MMP-9 and caspase3 mRNA and protein expression, and effectively inhibit the expression of induced genes and proteins in intracranial tumors; and iv) the inhibitory effect of vascular interventional embolization on the expression of MMP-2, MMP-9 and caspase3 may be associated with inhibition in patients with the AMPK expression, and reduce the expression of apoptotic protein Bcl-2/Bax.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial tumor is caused by many factors, and intracranial atherosclerosis-induced degradation of arterial wall and the occurrence of inflammatory reaction is the main reason. The treatment of intracranial hemangiomas by intracranial vascular embolization increased in the 1970s, and intracranial vascular embolization and craniotomy are the most common means of treatment of intracranial aneurysms ( 10 , 11 ). In this study, by comparing the impact of vascular interventional embolization and craniotomy on patients with intracranial aneurysms, the results showed that i) vascular interventional embolization can effectively increase the 3-year survival rate of patients with intracranial tumors, and significantly reduce postoperative adverse reactions; ii) vascular embolization can effectively reduce the levels of intravascular ROS and proinflammatory cytokines, and increase the level of inhibitors, which can effectively control the intracranial inflammatory response; iii) vascular embolization can effectively reduce the serum levels of MMP-2, MMP-9 and caspase3 mRNA and protein expression, and effectively inhibit the expression of induced genes and proteins in intracranial tumors; and iv) the inhibitory effect of vascular interventional embolization on the expression of MMP-2, MMP-9 and caspase3 may be associated with inhibition in patients with the AMPK expression, and reduce the expression of apoptotic protein Bcl-2/Bax.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of IA is reported to be approximately 5% in average [2]; for genetic disorders the phenotype prevalence and penetrance should be used to define the allele frequency cutoff [19]. Therefore, for the validation of reported UIA/SAH risk genes, we screened for low-frequency (MAF > 1 to 5%), rare (MAF > 0.1 to 1%), very rare (MAF ≤ 0.1%) and unknown variants (MAF = 0) in these genes [20,21], thereby including those variants with strong, intermediate as well as moderate effect size and penetrance [22]. For the identification of novel susceptibility genes in the family-based approach we searched for unknown variants (MAF = 0; with anticipated significant effect size/penetrance) shared by the affected family members.…”
Section: Exome Sequencing Variant Calling Filtering Strategies Varmentioning
confidence: 99%
“…Dysregulation of this signaling pathway is widely accepted to be central in the pathogenesis of hereditary aortopathies [45]. Numerous familial linkage and GWAS reporting on potential gene loci for IAs have been summarized elsewhere [18,21]. A genome-wide-linkage/ haplotype-association analysis revealed a strong evidence for a linkage of IAs to the chromosomal region 5q14.3 with a p value of 0.001 for marker D5S428; this DNA marker localizes ca.…”
Section: Genetic and Functional Aspects On Edil3 As An Uia/ Asah Riskmentioning
confidence: 99%
“…The prevalence of IA is 2–5% worldwide and approximately 7% in Chinese adults aged 35 to 75 years old 12. The rupture of an IA leads to subarachnoid hemorrhage (SAH), which is one of the most devastating known neurological conditions 3. Although the pathogenesis of IA has been explored for many years, the mechanisms of its formation, growth, and rupture remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%